A MARINE PROTECTED AREA DESIGN TO PROTECT THE BLUE SWIMMING CRAB POPULATION IN SALEMO ISLAND, SPERMONDE ARCHIPELAGO - Muh Saleh Nurdin; Fauziah Azmi; Teuku Fadlon Haser (Indonesian Fisheries Research Journal, 2022)
Blue swimming crab fishery in Salemo Island, Spermonde Archipelago, indicates overfishing. To ensure the sustainability of the blue swimming crab fishery, conservation effort through fishing prohibition needs to enforce. This research aimed to design a reservation area to protect the blue swimming crab resources. The study was conducted from May to July 2015. Creating a reserved area requires information on female berried crabs and larval abundance as the basic assumption that places containing the two information are the spawning ground. Information on female berried crabs in Salemo Island is readily available in the literature, while information on larval abundance must be obtained through this study before designing the reservation. Larvae of the blue swimming crabs were sampled using larval nets. Sampling was performed in three habitats: seagrass beds, coral reefs, and mangroves (estuaries). Differences between habitat’s larval abundance were analyzed using a Student T-test, while the reservation area was designed using Marxan Software. Total larvae captured during samplings were 236 individuals. Larvae were abundant in seagrass beds and coral reefs, making the two habitats suitable for the reserved area. The “no-take zone” area obtained from the analysis protects the biological parameters, less conflict with human activities, and provides minimum cost, which is fulfilled by Scenario 3.